In real life - Wang, Jen, 1984-; Doctorow, Cory. (New York : :01, First Second, 2014)
"Anda loves Coarsegold Online, the massively-multiplayer role playing game that she spends most of her free time on. It's a place where she can be a leader, a fighter, a hero. It's a place where she can meet people from all over the world, and make friends. But things become a lot more complicated when Anda befriends a gold farmer--a poor Chinese kid whose avatar in the game illegally collects valuable objects and then sells them to players from developed countries with money to burn. This behavior is strictly against the rules in Coarsegold, but Anda soon comes to realize that questions of right and wrong are a lot less straightforward when a real person's real livelihood is at stake"--Inside front cover.
"Adapted from a story by Cory Doctorow called 'Anda's game' first published on Salon.com in 2004"--Colophon.
Added title page title: IRL.
Booklist starred
Kirkus Review
Publisher's Weekly
Booklist starred, September 2014
Keywords: Fantasy games -- Comic books, strips, etc. -- Juvenile fiction; Internet games -- Comic books, strips, etc. -- Juvenile fiction; Women fantasy gamers -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Fantasy games -- Fiction; Internet games -- Fiction; Women fantasy gamers -- Fiction; Comic books, strips, etc; Fantasy games -- Comic books, strips, etc. -- Fiction; Graphic novels; Internet games -- Comic books, strips, etc. -- Fiction; Women fantasy gamers -- Comic books, strips, etc; Graphic novels